PRECODING ACTIVITIES TO IMPROVE STUDENT'S COMPUTATIONAL THINKING SKILLS - Dwijayani, Ni Made (Widyagogik, 2022)
Coding means telling the computer to do something. In order to achieve this, the coder must understand what the problem is and what the best solution is. One of the things needed is pre-coding skills, including computational thinking skills. This study aims to improve students' computational thinking skills as a pre-coding ability. This classroom action research was conducted at a public elementary school in Dauh Puri, Denpasar, involving 20 first grade students. Data were collected based on observations in working on activity sheets and the results of student work on activity sheets. The data that has been collected was analyzed by quantitative descriptive. The results of data analysis showed that the students' computational thinking ability increased from pre-cycle activities, cycle I and cycle II respectively from 47.70 % to 65.05% and increased again to 81.50%. This increase in scores indicates that students' computational thinking skills can be improved by using student age-appropriate activity sheets as the basis for coding skills without having to involve a computer.